2015
DOI: 10.1517/14656566.2016.1109633
|View full text |Cite
|
Sign up to set email alerts
|

An update on antimicrobial options for childhood community-acquired pneumonia: a critical appraisal of available evidence

Abstract: Amoxicillin is the preferred option to treat non-severe non-complicated CAP among children aged ≥2 months. Amoxicillin may be used to treat children in this age group with severe CAP if they do not require hospital assistance. If the patient warrants hospitalization, intravenous penicillin is the chosen option. Heterogeneity was high in the included trials, in regard to clinical inclusion criteria, use of radiological inclusion criteria, placebo use and masking. Higher quality evidence was found in the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
1
0
1
Order By: Relevance
“…50 Uma revisão sistemática publicada em 2016 analisou todos os ensaios clínicos randomizados, publicados até abril de 2015, nos quais as crianças com PAC foram tratadas com antibióticos e acompanhadas: 54 estudos foram incluídos, dos quais 13 avaliaram a eficácia da amoxicilina em pacientes não hospitalizados não graves e 8 avaliaram a eficácia da amoxicilina em pacientes hospitalizados. 56 Assim, a amoxicilina foi o antimicrobiano mais estudado, com a melhor abordagem metodológica e a evidência mais confiável. Dois regimes de doses diferentes foram comparados em um ensaio clínico conduzido em Salvador, Brasil: 820 crianças com PAC não grave foram aleatoriamente designadas para receber 50 mg/kg/dia de amoxicilina duas ou três vezes ao dia; esse foi um ensaio clínico randomizado, triplo--cego e controlado por placebo que mostrou equivalência na eficácia de ambos os regimes de tratamento.…”
Section: Tratamentounclassified
“…50 Uma revisão sistemática publicada em 2016 analisou todos os ensaios clínicos randomizados, publicados até abril de 2015, nos quais as crianças com PAC foram tratadas com antibióticos e acompanhadas: 54 estudos foram incluídos, dos quais 13 avaliaram a eficácia da amoxicilina em pacientes não hospitalizados não graves e 8 avaliaram a eficácia da amoxicilina em pacientes hospitalizados. 56 Assim, a amoxicilina foi o antimicrobiano mais estudado, com a melhor abordagem metodológica e a evidência mais confiável. Dois regimes de doses diferentes foram comparados em um ensaio clínico conduzido em Salvador, Brasil: 820 crianças com PAC não grave foram aleatoriamente designadas para receber 50 mg/kg/dia de amoxicilina duas ou três vezes ao dia; esse foi um ensaio clínico randomizado, triplo--cego e controlado por placebo que mostrou equivalência na eficácia de ambos os regimes de tratamento.…”
Section: Tratamentounclassified
“…50 A systematic review published in 2016 analyzed all randomized clinical trials, published until April 2015, where children with CAP were treated with antibiotics and followed up: 54 studies were included, out of which, 13 evaluated the efficacy of amoxicillin in non-severe nonhospitalized patients and eight evaluated the efficacy of amoxicillin in hospitalized patients. 56 Thus, amoxicillin was the most studied antimicrobial, with the best methodological approach and the most reliable evidence. Two different dose regimens were compared in a clinical trial conducted in Salvador, Brazil: 820 children with non-severe CAP were randomly assigned to receive 50 mg/kg/day of amoxicillin either twice or thrice a day; this was a placebo-controlled, randomized, triple-blinded clinical trial that showed equivalence on the efficacy of both regimens.…”
Section: Treatmentmentioning
confidence: 99%